Valoración del impacto ambiental de la generación distribuida de electricidad en la central eléctrica fuel oil bayamo 110 kv de Granma - Villavicencio Calvopiña, Jorge Iván (2018)
The present work was developed in the 110 kV Fuel Oil Power Plant Bayamo, with the purpose of proposing alternatives of improvements in the production processes for the generation of electrical energy and with this, to make a better management of the urban ecosystem. The application of the Life Cycle Analysis methodology is performed according to the requirements established in ISO 14040 (2009), through the Eco-indicator 99 and using the software Sima Pro 7.1. The evaluated environmental impacts are made based on a thorough inventory analysis with each of the inputs and outputs of the system under study. With the result that the stage of greatest contribution to environmental impact is concentrated in the generation area, it was demonstrated that the categories of greatest impact to the environment are the use of fossil fuels, the breathing of inorganic compounds, the use of the land , acidification / eutrophication, climate change and eco-toxicity.